2000
DOI: 10.1017/s0016672300004663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parentage upon growth in Ostrea edulis: evidence for inbreeding depression

Abstract: SummaryGenetic variability for growth was analysed in three populations of Ostrea edulis, selected for resistance to the protozoan parasite Bonamia ostreae. This study was undertaken first to determine the potential for selection for growth in populations that have never been selected for this character, and second to estimate heterosis versus inbreeding depression. Growth was monitored in culture for 10 months. The selected populations (namely S85-G3, S89I-G2 and S89W-G2), their crossbred population and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
(38 reference statements)
1
14
0
1
Order By: Relevance
“…This also strongly highlights the variance in reproductive success among the potential breeders, something that has also been demonstrated for salmonids (Herbinger et al 2006). High relatedness among progenies, as demonstrated by our pedigree reconstruction analyses, could have serious implications for the long-term management of hatchery stocks, rapidly leading to inbreeding depression (Bierne et al 1998;Naciri-Graven et al 2000;Taris et al 2007) due to a high genetic load in oysters (Launey and Hedgecock 2001). Recent studies reported high variance of reproductive success in oysters both in the wild (Li and Hedgecock 1998;Hedgecock et al 2007) and under aquaculture conditions (Hedgecock et al 1992;Boudry et al 2002;Taris et al 2007;Lallias et al, unpublished results).…”
Section: Loss Of Genetic Diversitysupporting
confidence: 70%
“…This also strongly highlights the variance in reproductive success among the potential breeders, something that has also been demonstrated for salmonids (Herbinger et al 2006). High relatedness among progenies, as demonstrated by our pedigree reconstruction analyses, could have serious implications for the long-term management of hatchery stocks, rapidly leading to inbreeding depression (Bierne et al 1998;Naciri-Graven et al 2000;Taris et al 2007) due to a high genetic load in oysters (Launey and Hedgecock 2001). Recent studies reported high variance of reproductive success in oysters both in the wild (Li and Hedgecock 1998;Hedgecock et al 2007) and under aquaculture conditions (Hedgecock et al 1992;Boudry et al 2002;Taris et al 2007;Lallias et al, unpublished results).…”
Section: Loss Of Genetic Diversitysupporting
confidence: 70%
“…Numbers on internal branches are bootstrap support values greater than 50% after 10,000 iterations. marine bivalves, positive correlations between multilocus heterozygosity and fitness-related traits were often observed in highly inbred families and populations of bivalves (Gaffney et al 1990, Hedgecock et al 1995, McGoldrick & Hedgecock 1997, Bierne et al 1998, David 1998, Naciri-Graven et al 2000, Launey & Hedgecock 2001, Hedgecock et al 2007. Reduction in heterozygosity, although undetectable in the first several generations of inbreeding (Hedgecock & Sly 1990), could become significant after continued use of a small numbers of individuals for spawning, which are drawn from stocks that are already showing reduced allelic diversity.…”
Section: Implications For C Ariakensis Stock Managementmentioning
confidence: 99%
“…Negative effects of inbreeding on larval survival in hatcheries have been reported for various species of bivalves, with larviparous species such as Ostrea edulis being particularly susceptible (Bierne et al 1998, Naciri-Graven et al 2000. The genetic contributions of parents in mass matings depends on sex ratios within the population and on the ability to synchronize gametogenesis.…”
Section: Introductionmentioning
confidence: 99%